Reconciling custom, citizenship and colonial legacies: Ni‐Vanuatu tertiary student attitudes to national identity. Issue 4 (23rd August 2013) - Clarke, Matthew; Leach, Michael; Scambary, James
Abstract Nation‐building remains a key challenge in Vanuatu. From the origins of this new nation in 1980, it was clear that creating a unifying sense of national identity and political community from multiple languages and diverse traditional cultures would be difficult. This paper presents new survey and focus group data on attitudes to national identity among tertiary students in Vanuatu. The survey identifies areas of common attitudes towards nationalism and national identity, shared by both Anglophone and Francophone Ni‐Vanuatu. However, despite the weakening ties between language of education and political affiliation over recent years, the findings suggest that there remain some key areas of strong association between socio‐linguistic background, and attitudes to the nation, and national identity. These findings cast new light on the attitudes of likely future elites towards regional, ethnic, intergenerational and linguistic fault lines in Vanuatu and the challenges of building a cohesive sense of political community and national identity.